ENHANCING SERVICE EFFICIENCY THROUGH AN EXCEL MACRO- BASED INFORMATION SYSTEM: EVIDENCE FROM SANKEN SAMARINDA SERVICE CENTER - Tandi Kadang; Tiara; Andi Nurhasanah; Angga Kusumah; Feti Fahmimroah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to develop an information system using Microsoft Excel Macros to improve service efficiency at the Sanken Samarinda Service Center. The background of this research lies in the operational condition that still relies heavily on manual record-keeping, resulting in data entry delays, calculation errors, and slow report generation. The development of this information system is expected to accelerate the administrative processes of sales and services while increasing data accuracy. The research applied a mixed-methods approach, employing observation, interviews, documentation, and literature review for data collection. The incremental model was used for system development, allowing design and testing to be carried out progressively. The findings indicate that implementing a Macro Excel-based system reduces data entry time by up to 50%, improves operational efficiency, and enables automatic and accurate report generation. In terms of effectiveness, the system successfully optimizes resource utilization and minimizes human error. These findings reinforce the theory of information technology efficiency, showing that simple software tools like Microsoft Excel can serve as economical and effective alternatives to support business process digitalization.